2023
DOI: 10.1039/d3se00045a
|View full text |Cite
|
Sign up to set email alerts
|

Structure elucidation of prot, alkali and dealkaline lignin(s) by NMR, FT-IR and Py-GC/MS: effect of solid acid and base catalysts

Abstract: Structural insight into lignin(s) helps in understanding its breaking behaviour, and is needed to overcome the real industrial lignin valorization problem. Here, one industrial lignin obtained from mixture of biomass...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
(89 reference statements)
0
8
0
Order By: Relevance
“…Further, the weight loss in the range of 100–500 °C was accredited to the decomposition of volatiles. The major loss in the range of 620–900 °C can be ascribed to the decomposition of the eggshell’s calcium carbonate and cracking of lignin linkages. , Consequently, the final carbon material was fabricated by pyrolyzing at 900 °C to ensure the complete decomposition of lignin and eggshell.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the weight loss in the range of 100–500 °C was accredited to the decomposition of volatiles. The major loss in the range of 620–900 °C can be ascribed to the decomposition of the eggshell’s calcium carbonate and cracking of lignin linkages. , Consequently, the final carbon material was fabricated by pyrolyzing at 900 °C to ensure the complete decomposition of lignin and eggshell.…”
Section: Resultsmentioning
confidence: 99%
“…12,13 In contrast, PEMWE has the advantage of a fast response under highly dynamic operating conditions, making it suitable for integration with intermittent renewable energy sources. [14][15][16] Therefore, PEMWE attracts unprecedented attention in green hydrogen production and is considered a more promising water electrolysis technology for the future.…”
Section: Ligang Fengmentioning
confidence: 99%
“…The generated electrons are transported to the surface of the cathode through the external power supply circuit, and the protons pass through the PEM to the cathode catalyst layer and combine with the electrons on the cathode surface to generate hydrogen (4H + + 4e À -2H 2 ). 12,15 Based on the understanding of the principles of PEMWE technology, it can be found that the catalyst layer is the core site for energy conversion through electrochemical reactions. 60,61 The development of low-cost, high-performance catalysts is still very crucial to promote the large-scale application of PEMWE.…”
Section: Pemwe Working Principlementioning
confidence: 99%
“…Recently, studies on energy storage and conversion devices, including fuel cells, secondary batteries, metal-air batteries, and water electrolysis have been attempted and increased progressively. [1][2][3][4][5] To improve the efficiency of the aforementioned devices, appropriate catalysts are required for applications. In addition, several devices require multiple catalysts for different reactions between the cathode and anode.…”
Section: Introductionmentioning
confidence: 99%